Thickness-dependent electrochemical response of plasma enhanced atomic layer deposited WS2 anodes in Na-ion battery. (1st November 2019) - Nandi, Dip K.; Yeo, Seungmin; Ansari, Mohd Zahid; Sinha, Soumyadeep; Cheon, Taehoon; Kwon, Jiseok; Kim, Hyungjun; Heo, Jaeyeong; Song, Taeseup; Kim, Soo-Hyun
Abstract: In spite of the promising future of the Sodium (Na)-ion batteries (NIBs), it still suffers with low specific capacity and stability mostly owing to the slow kinetics associated with Na ion. In this regard, transition metal sulfides (TMSs) are considered to be one of the best anode materials that can efficiently store Na ions not only owing to their graphite-like layered structure but also through conversion reactions facilitated by their multi-oxidation states. However, the poor cyclic stability of these TMSs attributed to the low electronic conductivity of the TMSs hinders the practical use. Therefore, understanding on an optimized mass loading (or physical dimensions) and configuration of such active electrode material are essential to improve the kinetics associated with Na-ion and electron pathway. To study this, plasma-enhanced atomic layer deposition (PEALD) is employed to grow WS2 using tungsten hexacarbonyl [W(CO)6 ] and H2 S plasma as a precursor and reactant, respectively. The thin films of WS2 deposited directly on stainless steel coin with varying ALD cycles (200–600) are then tested as anode in NIBs without any binder or conducting carbon. Two-stage growth mode is observed with increasing number of ALD cycles which leads to WS2 nano-flakes formation on top of a two-dimensional film of the same. Reversible conversion and intercalation reactions from the cyclic voltammetry measurements are evident for the electrochemical stability of these pristine-WS2 films. While the highest areal capacity of ∼58.8 μAh/cm 2 at a current density of 50 μA/cm 2, after 50 charge-discharge cycles, is achieved with 400 ALD cycles, the highest capacity retention (∼72.5%) is observed for the film deposited with minimum (200) ALD cycles under same conditions. However, the capacity as well as its retention degrades drastically when the number of ALD cycles is further increased beyond 400. In this study, we address a critical issue associated with WS2 as an anode material for NIBs which should be similarly true for other TMSs as well.